2017
DOI: 10.1038/s41598-017-05500-z
|View full text |Cite
|
Sign up to set email alerts
|

Oncolytic measles virus enhances antitumour responses of adoptive CD8+NKG2D+ cells in hepatocellular carcinoma treatment

Abstract: There is an urgent need for novel effective treatment for hepatocellular carcinoma (HCC). Oncolytic viruses (OVs) not only directly lyse malignant cells, but also induce potent antitumour immune responses. The potency and precise mechanisms of antitumour immune activation by attenuated measles virus remain unclear. In this study, we investigated the potency of the measles virus vaccine strain Edmonston (MV-Edm) in improving adoptive CD8+NKG2D+ cells for HCC treatment. We show that MV-Edm-infected HCC enhanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 46 publications
0
31
0
Order By: Relevance
“…RNA was extracted, purified and converted to cDNA using an oPlus kit and PrimeScript RT Master Mix (Takara Bio Inc., Naha, Japan) according to the manufacturer's protocol. 16 Quantitative real-time PCR was performed using a ViiA 7 real-time PCR system (Applied Biosystems, Thermo Fisher Scientific, Rockford, IL, USA) and SYBR Green PCR master mix. The primers used for real-time PCR were as follows: DEPDC1B forward 5′-AGCTACCAGGCTGTGGAATG-3′ and reverse 5′-AGCTCTTGAAACGACAGCGA-3′; GAP DH forward 5′-CCATGTTCGTCATGGGTGTGAACCA-3′ and reverse 5′-GCCAGTAGAGGCAGGGATGATGTTC-3′.…”
Section: Real-time Pcr (Qrt-pcr)mentioning
confidence: 99%
“…RNA was extracted, purified and converted to cDNA using an oPlus kit and PrimeScript RT Master Mix (Takara Bio Inc., Naha, Japan) according to the manufacturer's protocol. 16 Quantitative real-time PCR was performed using a ViiA 7 real-time PCR system (Applied Biosystems, Thermo Fisher Scientific, Rockford, IL, USA) and SYBR Green PCR master mix. The primers used for real-time PCR were as follows: DEPDC1B forward 5′-AGCTACCAGGCTGTGGAATG-3′ and reverse 5′-AGCTCTTGAAACGACAGCGA-3′; GAP DH forward 5′-CCATGTTCGTCATGGGTGTGAACCA-3′ and reverse 5′-GCCAGTAGAGGCAGGGATGATGTTC-3′.…”
Section: Real-time Pcr (Qrt-pcr)mentioning
confidence: 99%
“…Oncolytic viruses (OVs) have double functions of direct cytotoxicity and induction of effective anti-tumor immune responses [82]. The research reports from Chen et al [83] showed that the intratumoral injection of measles virus vaccine strain Edmonston (MV-EDM) could induce the expression of specific ligand MICA and MICB on the surface of hepatoma cells, and thereby could significantly enhance the cytotoxicity of CD8 + NKG2D + T cells to hepatocellular carcinoma. It could also enhance the expression of FasL in CD8 + NKG2D + cells, but had no effect on the expression of Fas in hepatoma cells.…”
Section: Fasl Expressed On Nk Cells Exerts Anti-hepatocarcinoma Activmentioning
confidence: 99%
“…Therapeutic administration of oncolytic viruses (OV) into tumors promotes strong antiviral immune response accompanied by the production of cytokines such as type-1 interferons and chemokines. 17 , 26-28 Type-1 interferons promote the expression of PD-L1 on the surface of cancer cells, while chemokines like CCL3 and CCL4 attract immune cells which often express PD-1 or CTLA-4. 29-32 Thus, antiviral immunological events inflame the tumor and make it ‘hot’.…”
mentioning
confidence: 99%